The Effect of Trust and Atitude on Purchase Intentions Mediated by Electronic Word-Of-Mouth (EWOM) in the Culinary Industry on Instagram - Oscar, Oscar; Louis, Vincent (Budapest International Research and Critics University, 2021)
The research and to see the relationship between 4 variables, namely purchase intention, eWOM, trust, and attitude on Instagram especially in the culinary industry. This study aims to 1) find out the effect of trust to eWOM, 2) find out the effect of attitude to eWOM, 3) find out the effect of trust on purchase intentions mediated by eWOM, 4) find out the effect of attitude to eWOM mediated by purchase intentions, 5) find out the effect of trust to purchase intention, and 6) find out the effect of attitude to purchase intention. This research was conducted quantitative research by distributing questionnaires in the area of Jakarta, Indonesia. 175 respondents were obtained, which were divided by sex, age, and education. Processing data with the PLS-SEM statistical method with SmartPLS 3 version 3.2.8. After the data obtained and processed, some conclusions are found, 1) trust has a positive and significant effect on eWOM, 2) attitude has a positive and significant effect on eWOM, 3) the effect of trust to purchase intention that is mediated by eWOM is negative and insignificant, 4) the effect of attitude to purchase intention that is mediated by eWOM is negative and insignificant, 5) trust has a positive and significant effect on purchase intention, and 6) attitude has a positive and significant effect on purchase intention . In this study the most dominant thing is the effect of attitude on purchase intention.